Hubungan Pengetahuan Ibu Gizi Seimbang dengan Kejadian Stunting pada Balita di Wilayah Desa Jambu Kecamatan Mlonggo Kabupaten Jepara - Yuanita Kusuma Ningrum; Ratna Ratna; Akbar Amin Abdullah (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
The prevalence of stunting globally in 2021 reached 171 million to 314 million. In Indonesia, the results of the Indonesian Nutritional Status Survey (SSGI) showed that the stunting rate in 2019 was 27.7%, in 2021 it was 24.4%, and in 2022 it was 21.4%. Child stunting is a health concern in Indonesia. Causes of stunting in children include poor nutrition, low exclusive breastfeeding rates, low birth weight (LBW), and maternal factors in providing nutrition from pregnancy to 59 months of age. Research reports that stunting is influenced by parents' lack of knowledge about balanced nutrition. Knowledge plays a vital role in the life and development of individuals and society.Purpose This study aims to determine the relationship between maternal knowledge about balanced nutrition and the incidence of stunting in toddlers in the Jambu Village area, Mlonggo District, Jepara City. Method This research is a quantitative correlational study with a cross-sectional design. The population in this study were mothers with toddlers in the Jambu Village area, Mlonggo District. The sampling technique used total sampling to obtain a sample of 34 respondents. Measurement of the level of knowledge of nutritional balance by providing questions with multiple choices of true and false and for stunting using Microtois and Anthropometric Table. Data processing using SPSS with a computer using the Spearman Rho statistical test.The results of the study showed that the majority of respondents had good nutritional balance knowledge, amounting to 16 (47.1%), while 17 (50.0%) respondents did not experience stunting.There is a relationship between maternal knowledge about balanced nutrition and the incidence of stunting in toddlers in Jambu Village, Mlonggo District, Jepara Regency.